Determinants Of Cash Holding: Studi Empiris pada Perusahaan Wholesale Terdaftar di BEI Tahun 2017-2021 - Yustiranda Wahyuni; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2023)
The purpose of this study was to determine and analyze the influence of operating cash flow and company size on the cash holdings. This research uses quantitative methods with 2017-2021 observation years. The research sample consisted of 28 wholesale sub-sector companies listed on the Indonesia Stock Exchange, while the method used was purposive sampling, with a total sample of 140 samples. The type of data in this study is secondary data obtained from the Indonesia Stock Exchange in the form of an annual report. The analytical method used is multiple regression and path analysis to test the hypothesis which is assisted by using the SPSS 22. The results showed operating cash flow have a positive and significant effect on the cash holding, while the company size has a positive but not significant effect on the cash holding.